Community Preparedness, Acceptability, and Uptake of UTT Services in PHC Facilities - Dzunisani B. Mhlari; Mathildah M. Mokgatle; Ntlogeleng M. Mogale; Raikane J. Seretlo (SciMedicine Journal, 2023)
Background: The Universal Test and Treat (UTT) strategy ensures that people test and initiate early treatment in health facilities. Communities have benefited from this strategy to help manage HIV and prevent the spread of the disease, but the way people perceive the strategy and their experiences of testing and initiating antiretroviral therapy (ART) on the same day have an impact on their remaining on treatment and on their adherence. The aim of the study: The aim of this study was to describe the perceptions and explore the experiences of newly enrolled patients regarding the UTT strategy employed in health facilities in Kgetleng sub-district. Method: This is a qualitative study that used in-depth interviews to describe the perceptions and explore the experiences of newly enrolled patients regarding the UTT strategy employed in health facilities in Kgetleng sub-district. The twenty-seven participants were purposefully selected from three health facilities in the sub-district. The data were collected and transcribed verbatim. The transcripts were analyzed using thematic content analysis. Results: The participants reported that they were not knowledgeable about or aware of the strategy until they tested positive in their clinics. HIV testing services (HTS) are still underused, as the participants presented to the facilities only when they were seriously ill, had various symptoms, or were pregnant. They described accepting their status and treatment because they were already sick, and there was nothing that they could do but take treatment. Despite the different emotions they experienced, the participants were able to accept their treatment and their status. Surprisingly, those who were still in denial also accepted treatment. Some were able to disclose and received support from their family, partners, and friends, but others had not disclosed. The data also showed their fear of stigmatization if they were seen coming to the clinic frequently. Conclusion: Being diagnosed with the human immunodeficiency virus (HIV) is still a source of embarrassment. There is still a need to educate communities about the virus, encourage them to use HTS, and empower them with information to minimize stigma and promote social support.